First Isolation of New Canine Parvovirus 2a from Tibetan Mastiff and Global Analysis of the Full-Length VP2 Gene of Canine Parvoviruses 2 in China - Zhong, Zhijun (MDPI, 2014)
Canine parvovirus 2 (CPV-2) was first identified in 1978, and is responsible for classic parvoviral enteritis. Despite the widespread vaccination of domestic carnivores, CPVs have remained important pathogens of domestic and wild carnivores. In this study, we isolated CPV-2 from Tibetan mastiffs and performed a global analysis of the complete VP2 gene sequences of CPV-2 strains in China. Six isolates were typed as new CPV-2a, according to key amino acid positions. On a phylogenetic tree, these six sequences formed a distinct clade. Five isolates occurred on the same branch as KF785794 from China and GQ379049 from Thailand; CPV-LS-ZA1 formed a separate subgroup with FJ435347 from China. One hundred ninety-eight sequences from various parts of China and the six sequences isolated here formed seven distinct clusters, indicating the high diversity of CPVs in China. Of 204 VP2 sequences, 183 (91.04%) encoded the mutation Ser297Ala, regardless of the antigenic type, implying that most Chinese CPV-2 strains contain the VP2 mutation Ser297Ala. However, the biological significance of this change from prototype CPV-2a/2b to new CPV-2a/2b types remains unclear. This study is the first to isolate new CPV-2a from the Tibetan mastiff. Our data show that new CPV-2a/2b variants are now circulating in China.